Predicting The Inflation Rate in The Kingdom of Saudi Arabia Using Time Series Analysis From 2000 To 2023 - Ismail, Awaidia Mohammad (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to predict the inflation rate in Saudi Arabia using time series analysis and the Box-Jenkins model (ARIMA). Data were obtained from the Saudi Central Bank and analyzed using an analytical, quantitative, and applied approach. Linear models were used and compared to select the best model. The results showed that the data is stable. The best model for prediction is the quadratic model and the ARIMA model (1,0,0). Based on the results, the inflation rate is expected to reach 2.47% in 2022 and 2.59% in 2023. The study recommends adopting these models to predict future rates and developing financial policies based on these predictions. Adopting the predictions to formulate future plans to reduce the inflation rate. Keywords: inflation rate, time series, Box-Jenkins model, ARIMA, economic forecasting.